Changing Attitudes Towards CSR and Youth Among SMEs - Allgaier, Hildengard (2012)
The purpose of this paper is to apply a Corporate Social Responsibility perspective in the analysis of SME engagement with young people. Considering that small and medium enterprises in the UK face serious skills shortages, graduates are an important potential resource to increase company competitiveness; they are, moreover, an important social asset in the development of the local community and possibly the broader British economy.